CdS Quantum Dot‐Sensitized Vertical TiO2 Nanorod Arrays by a Simple Linker‐Assisted SILAR Method. Issue 10 (8th July 2015) - Wei, Lidong; Li, Fen; Hu, Sujuan; Li, Haijin; Chi, Bo; Pu, Jian; Jian, Li
Abstract : The homogeneously deposition of quantum dots (QDs) on the mesoporous or one‐dimensional TiO2 film with a well‐covered layer has become one major challenge in quantum dot‐sensitized solar cell (QDSSC). In this study, one‐dimensional TiO2 nanorod arrays based photoanode prepared by a simple linker‐assisted SILAR method is studied. The influence of the short organic ligand (TGA) on the homogeneity of QDs on TiO2 nanorod arrays is discussed and the photoelectrochemical performance of QDSSC is evaluated by UV–vis absorbance spectroscopy, current–voltage performance and electrochemical impedance spectroscopy. The results show that the TGA ligand can act as an efficient bridge between CdS QDs and TiO2, whereas the content and particle size of the QDs can be easily tuned by controlling the dipping time and SILAR cycle. Owing to the presence of TGA, the charge‐transfer rate at CdS QDs and TiO2 interfacial region is noticeable enhanced.